COMPARATION OF INTERNATIONAL COPYRIGHT LAW IN INDONESIA COUNTRIES - HONGKONG - SINGGAPORE - MALAYSIA AND THAILAND VIEWED FROM THE ASPECT OF CRIMINAL SANCTIONS ON CORPORATION - Edi Ribut Harwanto (Universitas Muhammadiyah Metro, 2019)
Copyright Law No. 28 of 2014 concerning Copyright in Indonesia has been ratified since 2014, and came into force and can be implemented or operationalized after two years later in 2016. The main problems that arise with the application of the Copyright Act Cipta in Indonesia there are other issues related to juridical issues regarding the formulation of criminal provisions and related to the problem of unclear issues regarding the formulation of criminal offense qualifications or unclear violations, determination of the subject of corporate law is not regulated, corporate criminal sanctions are not regulated, formulation of sanctions for sanctions that are not clear, against criminal offenses in the Copyright Act. Juridical problems in the Copyright Act in Indonesia will have an impact on the implementation and operation of the current and future Copyright Laws. Furthermore, a discussion on the comparative policy formulation of criminal provisions against corporate legal entities in Indonesia with the Copyright Act in other countries. Copyright Regulations, except for the Indonesian state, do not regulate criminal sanctions against corporations, while Malaysia, Singgapura, Malaysia, Hong Kong and Thailand all regulate criminal sanctions against corporations and include them as strict legal subjects in their material and formal laws. That, proving that, copyright infringement in the eyes of foreign countries is considered important and crucial, so it needs to be regulated in the policy formulation of criminal provisions in that country in order to protect copyright holders, related rights and performers of copyright. Unlike the Copyright Act in Indonesia, only regulates the legal subject of individuals, while corporate legal entities are only referred to in the juridical definition in general provisions of the Copyright Act only, but the provisions in the formulation policy of criminal provisions are not clearly and clearly regulated. Though it is clear that criminal liability sanctions between individuals with criminal sanctions corporate legal entities differ in the imposition of sanctions. Corporations are legal entities created by law. The body that it creates consists of a